Alternative splicing during human monocyte differentiation - Wong, Michelle Mei Su (2016)
Alternative splicing (AS) is an important step in post-transcriptional gene regulation and plays a role in many developmental processes including cell differentiation. However, AS during monocyte differentiation has yet to be fully characterised. To identify these AS changes, RNA sequencing (RNA-seq) was employed. However, how much of these data can we trust? In this study, we confirmed the RNA-seq data through reverse transcription polymerase chain reaction (RT-PCR) and found that the targets were mostly validated (16 out of 20) with few exceptions (4 out of 20). A positive correlation was drawn between RT-PCR and RNA-seq. Fifteen of the validated AS were also conserved between THP-1 cell line and primary monocytes/macrophages. This supports the usage of these tools in shortlisting targets for advanced studies. In addition, we used MBNL1 and DNM2 as a case study for mutually exclusive exons (MXE). Preliminarily, overexpression and knockdown of MBNL1 strongly suggested that this factor regulates DNM2 MXE by favouring exon 10a inclusion over 10b. Data strongly indicated MBNL1 as a repressor of DNM2 MXE in 10b but the mechanism was still unidentified. The AS change in the case study was not conserved in primary monocytes but it could help elucidate MXE mechanisms in humans.